Key considerations in the modeling of tropical maritime microwave attenuations - Lee, Yee Hui (2015)
This paper presents some key considerations for modeling of over-sea radio-wave propagations in 5 GHz band. The summarized information is based on a series of measurement campaigns which were recently carried out in the tropical maritime environments near Singapore. Multiray propagations and ducting of radio waves have been highlighted and considered in over-sea path loss modeling and prediction. It is noted that the sea-surface reflection is an important contribution in the received field, while the duct layers could enhance the radio-wave propagations. Our studies also show that the refracted ray inside evaporation duct could be a strong ray for short-range near sea-surface applications and needs to be properly evaluated.